Model Tata Kelola Strategis Destinasi Multi-Fungsi: Integrasi Nilai Sakral Keagamaan dan Kearifan Lokal di Situs Taman Purbakala Pugung Raharjo - Roliyanti, Roliyanti; Riyanto, Kuncoro Budi; Febriyanto, Febriyanto (Jurnal Penelitian Agama Hindu, 2026)
The Pugung Raharjo Archaeological Park in East Lampung faces complex managerial challenges as a multi-functional destination encompassing conservation, tourism, and ritual space. This study aims to formulate a participatory strategic governance model to balance these three functions, particularly in accommodating the sacred values of megalithic remains actively used for Hindu spiritual rites. A qualitative method with a multi-stakeholder case study approach was employed. Primary data were gathered through in-depth interviews with the Cultural Heritage Preservation Office (BPK) Region VII, the East Lampung Regency Government, site guardians, and the Hindu community. Data were analyzed using the Miles and Huberman interactive method, grounded in Stakeholder Theory. The findings reveal that while no open conflicts have occurred, the current operational management of the site remains sporadic, relying on "informal customs" and ad-hoc communication between institutions. A significant gap was identified where the Hindu community, despite possessing high urgency and legitimacy regarding the site, has not been formally involved in strategic decision-making by central authorities. This lack of formalization poses a potential risk to the degradation of sacred values and administrative uncertainty. In conclusion, this research proposes a "Cultural Value-Based Strategic Governance Model" which advocates for the establishment of a Multi-Functional Governance Forum. This model offers solutions through the formalization of stakeholder participation, the integration of Conservation Religious Standard Operating Procedures (SOPs), and the strengthening of the site’s religious brand equity. Implementing this model is expected to ensure the physical preservation of cultural heritage while respecting its function as a living spiritual space.